Non-genomic steroid signaling through the mineralocorticoid receptor: Involvement of a membrane-associated receptor?. (5th February 2022) - Karst, Henk; den Boon, Femke S.; Vervoort, Niek; Adrian, Max; Kapitein, Lukas C.; Joëls, Marian
Abstract: Corticosteroid receptors in the mammalian brain mediate genomic as well as non-genomic actions. Although receptors mediating genomic actions were already cloned 35 years ago, it remains unclear whether the same molecules are responsible for the non-genomic actions or that the latter involve a separate class of receptors. Here we focus on one type of corticosteroid receptors, i.e. the mineralocorticoid receptor (MR). We summarize some of the known properties and the current insight in the localization of the MR in peripheral cells and neurons, especially in relation to non-genomic signaling. Previous studies from our own and other labs provided evidence that MRs mediating non-genomic actions are identical to the ones involved in genomic signaling, but may be translocated to the plasma cell membrane instead of the nucleus. With fixed cell imaging and live cell imaging techniques we tried to visualize these presumed membrane-associated MRs, using antibodies or overexpression of MR-GFP in COS7 and hippocampal cultured neurons. Despite the physiological evidence for MR location in or close to the cell membrane, we could not convincingly visualize membrane localization of endogenous MRs or GFP-MR molecules. However, we did find punctae of labeled antibodies intracellularly, which might indicate transactivating spots of MR near the membrane. We also found some evidence for trafficking of MR via beta-arrestins. In beta-arrestin knockout mice, we didn't observe metaplasticity in the basolateral amygdala anymore, indicating that internalization of MRs could play a role during corticosterone activation. Furthermore, we speculate that membrane-associated MRs could act indirectly via activating other membrane located structures like e.g. GPER and/or receptor tyrosine kinases.